Delayed presentation with sigmoid perforation: a gut feeling that something is wrong - McElhatton, Claire P.; Cross, Trent (International Surgery Journal, 2023)
Blunt abdominal trauma (BAT) resulting in delayed colonic perforation is uncommon, even more so in the case of an isolated injury. This case report describes a presentation with a contained sigmoid perforation six days after low impact BAT which was managed non-operatively.